TECHNOLOGY VS NATURE: HUMAN ERROR IN DEALING WITH NATURE IN CRICHTON’S JURASSIC PARK - Soelistyo, Liliek; Prasasti, Sarah (k@ta: A Biannual Publication on the Study of Language and Literature, 2004)
Witnessing the euphoria of the era of biotechnology in the late twentieth century, Crichton exposes the theme of biotechnology in his works. In Jurassic Park, he voices his concern about the impact of the use of biotechnology to preserve nature and its living creatures. He further describes how the purpose of preserving nature and the creatures has turned out to be destructive. This article discusses Crichton’s main character, Hammond, who attempts to control nature by genetically recreating the extinct fossil animals. It seems that the attempt ignores his human limitations. Although he is confident that has been equipped with the technology, he forgets to get along with nature. His way of using technology to accomplish his purpose proves not to be in harmony with nature. As a consequence, nature fights back. And he is conquered.